2014
DOI: 10.1111/anec.12132
|View full text |Cite
|
Sign up to set email alerts
|

P-Wave Morphology Is Unaffected by Atrial Size: A Study in Healthy Athletes

Abstract: We demonstrated that P-wave morphology does not depend on the size of the atria in young, healthy athletes, and that PTF is not a reliable marker of left atrial enlargement in the current population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Indeed, some of the genes identified in the analyses of P-wave duration are more likely to produce “electrical” disturbances ( SCN5A, SCN10A, HCN1, CAV1/CAV2, EPAS1, CAND2 , and CAMK2D ), while a selection of the genes identified in the analyses of P-wave terminal force are more likely to cause “structural” changes ( TBX5, ALPK3/NMB, MYH6, and SPON1) . However, recent studies have reported that P-wave terminal force was not associated with left atrial enlargement on echocardiography 34 or computed tomography volume measurement. 35 In a sample of 275 middle-aged Americans referred to cardiovascular magnetic resonance imaging between 2001–2004, electrocardiographic P-wave terminal force (negative P terminal force in V1 > 0.04 s × mm) had high specificity (88%), but low sensitivity (37%) and positive predictive value (47%) for left atrial enlargement, compared to volumetric assessment of left atrial size.…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, some of the genes identified in the analyses of P-wave duration are more likely to produce “electrical” disturbances ( SCN5A, SCN10A, HCN1, CAV1/CAV2, EPAS1, CAND2 , and CAMK2D ), while a selection of the genes identified in the analyses of P-wave terminal force are more likely to cause “structural” changes ( TBX5, ALPK3/NMB, MYH6, and SPON1) . However, recent studies have reported that P-wave terminal force was not associated with left atrial enlargement on echocardiography 34 or computed tomography volume measurement. 35 In a sample of 275 middle-aged Americans referred to cardiovascular magnetic resonance imaging between 2001–2004, electrocardiographic P-wave terminal force (negative P terminal force in V1 > 0.04 s × mm) had high specificity (88%), but low sensitivity (37%) and positive predictive value (47%) for left atrial enlargement, compared to volumetric assessment of left atrial size.…”
Section: Discussionmentioning
confidence: 91%
“…Although one may speculate that factors other than electrical activation routes affect P-wave morphology, our group has previously shown that P-wave morphology does not depend on atrial size in healthy subjects with physiologically enlarged atria [ 5 ] and that the physiological anatomical variation in transverse orientation of the LA does not influence P-wave morphology [ 6 ]. The present study was primarily designed to investigate if different pressures in the LA and right atrium (RA) are associated with different orthogonal P-wave morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…Varying P wave morphology is known as wandering pacemaker and consistent with a high vagal tone varying the location of the atrial pacemaker region (Boineau et al 1978). P waves were frequently biphasic, which reflect type 2 or type 3 P waves in humans and longer P wave durations are recorded with type 2 P wave morphology (Petersson et al 2014). Whereas in dogs, biphasic P waves are usually associated with atrial enlargement and disease (Cote 2010), no association of type 2 or type 3 P waves with left atrial enlargement was detected in a group of healthy athletes (Petersson et al 2014).…”
mentioning
confidence: 99%
“…P waves were frequently biphasic, which reflect type 2 or type 3 P waves in humans and longer P wave durations are recorded with type 2 P wave morphology (Petersson et al 2014). Whereas in dogs, biphasic P waves are usually associated with atrial enlargement and disease (Cote 2010), no association of type 2 or type 3 P waves with left atrial enlargement was detected in a group of healthy athletes (Petersson et al 2014). Seals might have type 2 or type 3 P waves; however, a cardiac disease causing enlarged atria and interatrial conduction disturbances cannot be excluded, as echocardiography was not performed.…”
mentioning
confidence: 99%
See 1 more Smart Citation